Discovery and engineering of a 1-butanol biosensor in Saccharomyces cerevisiae. (December 2017) - Shi, Shuobo; Choi, Yook Wah; Zhao, Huimin; Tan, Meng How; Ang, Ee Lui
Graphical abstract: Highlights: A universal method was adopted to effectively identify biosensors for any metabolite. Transcriptomic changes were analysed when S. cerevisiae was exposed to alcohols. Promoters were identified that responded specifically to 1-butanol. The promoter-based biosensors could distinguish varied 1-butanol production levels. Abstract: The present study aimed to develop a universal methodology for the discovery of biosensors sensitive to particular stresses or metabolites by using a transcriptome analysis, in order to address the need for in vivo biosensors to drive the engineering of microbial cell factories. The method was successfully applied to the discovery of 1-butanol sensors. In particular, the genome-wide transcriptome profiling of S. cerevisiae exposed to three similar short-chain alcohols, 1-butanol, 1-propanol, and ethanol, identified genes that were differentially expressed only under the treatment of 1-butanol. From these candidates, two promoters that responded specifically to 1-butanol were characterized in a dose-dependent manner and were used to distinguish differences in production levels among different 1-butanol producer strains. This strategy opens up new opportunities for the discovery of promoter-based biosensors and can potentially be used to identify biosensors for any metabolite that causes cellular transcriptomic changes.